Strategi Komunikasi Krisis Shopee Kepada Penjual Atas Kebijakan Pembatasan Subsidi Ongkir - Muhammad Chandra Wicaksana; Fitrinanda An Nur (MUKASI: Jurnal Ilmu Komunikasi, 2025)
Shopee's shipping subsidy strategy has attracted the government's attention as it is considered to affect fair competition in the e-commerce sector. The government views excessive shipping subsidy as potentially creating an unbalanced competitive environment for other businesses with limited resources, including local SMEs that rely on the marketplace ecosystem for sales. Therefore, this study aims to analyze the crisis communication strategy implemented by Shopee toward sellers in response to the government's policy restricting shipping subsidies. The primary focus is on the form of strategy employed and the patterns of messages communicated. Using the Situational Crisis Communication Theory (SCCT) approach, this study explores the categories of crisis communication strategies that emerge in Shopee's response, particularly in the official Shopee app's Help Center. The research findings indicate that the government's policy to restrict shipping subsidies places Shopee in the Victim Cluster, meaning it is directly impacted by external policies beyond the company's internal control. In addition, Shopee did not use a denial strategy, but rather emphasized a diminish and rebuild approach to reduce negative perceptions while maintaining the trust of its seller partners. These findings are expected to contribute to the development of crisis communication theory and serve as a practical reference for e-commerce players in dealing with crises caused by external policy changes.